A novel approach for the fastest MPPT tracking algorithm for a PV array fed BLDC motor driven air conditioning system - S Munisekhar; G.V Marutheswar; P Sujatha; K R Vadivelu (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The paper presents a modified constant voltage (MACV) maximum power tracking algorithm approach for PV array fed brushless DC (BLDC) motor drive for air conditioning application. The proposed algorithm tracks the power instantaneously for sudden changes in solar radiation. The PV power is fed to Voltage source inverter directly without conventional dc dc converter there by reducing the overall cost and high frequency switching losses and efficiency of the system is improved by reducing number of power conversion stages. The appropriateness of the voltage and current controller for PV fed BLDC motor for cooling applications is verified for dynamic changes of solar radiation. The proposed system is designed and modelled and results are verified using MATLAB/SIMULINK software.